A Systematic Review of Telemedicine in Pediatrics Evidence from Randomized Controlled Trials - Atnang, Muhammad; Samsidar, Samsidar; Bachri Mustamin, Syaiful (Journal of Scientific Insights, 2024)
Telemedicine has emerged as an important innovation in pediatric health care delivery, particularly in addressing issues of accessibility and quality of care. This systematic review focused on randomized controlled trials (RCTs) conducted over the last decade to assess the effectiveness of telemedicine in pediatric care. This review identified that telemedicine increases healthcare accessibility, increases patient satisfaction, and contributes to favorable treatment outcomes across a variety of health conditions. However, a significant gap identified was the lack of an up-to-date systematic review evaluating the current evidence regarding telemedicine in pediatrics. In response to this gap, this study provides a systematic and comprehensive evaluation, without using a specific theoretical framework, but rather focusing on the integration of recent evidence. Amid ongoing debate regarding the effectiveness of telemedicine in the pediatric setting, this review emphasizes the need for more RCTs to fill gaps in the existing literature. Overall, this literature review directs the future research agenda by highlighting the need for a more holistic and integrated approach to the utilization of telemedicine in pediatrics. With a focus on improving the quality of services and developing adequate policies, this research aims to make a significant contribution to the understanding and implementation of telemedicine in the future.